Knowledge Assessment of Hospital Nursing Staff in Saudi Arabia Regarding Clostridioides difficile Infection: A Descriptive Cross-Sectional Study - Abdulrhman Albougami; Saeed S. Banawas (Nursing Reports)
Clostridioides difficile (C. difficile), a gram-positive, spore-forming bacillus, has emerged as a leading cause of healthcare-associated infections, significantly contributing to infectious diarrhea and increasing healthcare costs. This descriptive, cross-sectional study was conducted among Saudi Arabian nursing staff from July to December 2023 to assess their knowledge and practices related to the diagnosis and management of C. difficile infection (CDI). Data were collected using a modified questionnaire. Overall, 358 nurses were surveyed, and 66% reported knowledge of C. difficile procedures. However, only 30.4% of the respondents correctly classified C. difficile as an anaerobic bacillus, while 42.2% were aware of the organism’s common occurrence in healthy adult volunteers. Additionally, 55.6% of respondents were aware of risk factors and 48.9% could name typical medicines that might cause illness. Only 24.0% acknowledged the cytotoxin test as the gold standard for detection, 26.8% identified hand washing with water and soap as an effective method to prevent the transmission of CDI, and 36.3% identified oral metronidazole as the first-line treatment for CDI. In summary, this study revealed a significant lack of awareness among nurses in Saudi Arabia regarding various aspects of CDI, emphasizing the need for improved education and training to address the knowledge gaps and quality of patient care.